Pertanggungjawaban Biaya Refund Produk Perspektif Maslahah Mursalah: Studi Kasus Marketplace Tokopedia - Aidil Iza Mahendra; Abdurrahman Harahap (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The rapid development of e-commerce in Indonesia, especially through the Tokopedia platform, has raised new issues related to the accountability of product refund costs. One of the problems is the burden of product return costs which are often charged to buyers, even though the error is not theirs. This study aims to normatively examine the product return mechanism on Tokopedia and determine the most appropriate party to bear the refund costs based on the principle of maslahah mursalah. The method used is a normative approach with a descriptive-analytical method, through a conceptual approach and an approach to relevant laws and regulations. The results of the study show that there is still inconsistency in the implementation of Tokopedia's refund policy, especially in terms of charging shipping costs. From the perspective of maslahah mursalah, charging costs to innocent parties is contrary to the principles of justice and protection of property (hifz al-mal). Therefore, a fairer and firmer refund policy is needed, both from the perspective of the marketplace platform and government regulations, in order to create consumer protection that is oriented towards the public interest in digital transactions.